2013
DOI: 10.4103/0971-5851.116194
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis at pediatric age, now time to think: Series of two cases

Abstract: The younger generation is consuming areca nut and areca nut products, which is coming in the market with different multicolored attractive pouches and easily available in each and every corner of the road. For the children from the lower socioeconomic strata, areca nut use is rampant. Alarmingly, it has been seen that the highest period of risk for engaging in areca nut alone is between the ages of 5 and 12. Oral submucous fibrosis associated with areca nut in children is a great concern for the Society and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
10
1
Order By: Relevance
“…Areca nut chewing are the dominant factor in OSF etiology and it is used as fourth harmful habit in the world after tobacco, alcohol and cafein (58). The use of Areca nut is widely preferred, especially in India, Western Pacific, South and Southeast Asia (21,59). The sale of Areca nut products in attractive and coloured packages in general public areas in recent years has lead to an increase prevalence of OSF in young populations.…”
Section: Oral Erythroplakiamentioning
confidence: 99%
See 3 more Smart Citations
“…Areca nut chewing are the dominant factor in OSF etiology and it is used as fourth harmful habit in the world after tobacco, alcohol and cafein (58). The use of Areca nut is widely preferred, especially in India, Western Pacific, South and Southeast Asia (21,59). The sale of Areca nut products in attractive and coloured packages in general public areas in recent years has lead to an increase prevalence of OSF in young populations.…”
Section: Oral Erythroplakiamentioning
confidence: 99%
“…The sale of Areca nut products in attractive and coloured packages in general public areas in recent years has lead to an increase prevalence of OSF in young populations. The addiction of areca nut and the increased risk of OSF especially in children aged 5-12 cause great concerns (21). Gupta et al (21), in a case study of two children aged 10 and 11 years, reported that children were chewing areca nut for 6-7 years and main clinical findings were limitation of mouth opening, burning oral mucosa and poor oral hygiene.…”
Section: Oral Erythroplakiamentioning
confidence: 99%
See 2 more Smart Citations
“…[8] OSMF may be defined as a slowly progressing disease, in which the fibrous bands form in the oral mucosa, ultimately leading to severe restriction of movement of the mouth including the tongue. [8,9] The highest incidence is seen in South East Asians and has been associated with betel nut chewing. This condition is most commonly seen in young adults, in the second to fourth decade of their life.…”
Section: Introductionmentioning
confidence: 99%